Teacher effectiveness in academic research writing: An exploratory factor analysis - De Ramos, Jennifer Tan (Animo Repository, 2011)
The study was conducted to examine the factors of teaching effectiveness for possible application to research writing teacher effectiveness. Three existing studies on teacher assessments served as basis for the construction of a 100-item questionnaire administered to 324 students of seven research writing classes at a university in Manila. Using exploratory factor analysis of eleven teacher assessment domains, the study was able to reduce the factors into four structures – social interaction, clear feedback, mastery of content, and authority. Means, standard deviations as well as Pearson correlation among the four factor structures were also obtained. With a mean of 59.6, social interaction was the first in the four categories. This was followed by mastery at 54.6, clear feedback at 47.8 and authority at 32.3. The findings have pedagogical and administrative implications.